Anti-biofilm and anti-quorum sensing activities of galloylquinic acid against clinical isolates of multidrug-resistant Pseudomonas aeruginosa in open wound infection: in vitro and in vivo efficacy studies - Lamiaa A. Al-Maddboly; Mohamed Abd El-Salam; Jairo K. Bastos; Eiman A. Hasby; Ivan Kushkevych; Rasha M. El-Morsi (BMC Microbiology)
Abstract Background Pseudomonas aeruginosa can proliferate in immunocompromised individuals, forming biofilms that increase antibiotic resistance. This bacterium poses a significant global health risk due to its resistance to human defenses, antibiotics, and various environmental stresses. The objective of this study was to evaluate the antibacterial, anti-biofilm, and anti-quorum sensing activities of galloylquinic acid compounds (GQAs) extracted from Copaifera lucens leaves against clinical isolates of multidrug-resistant (MDR) P. aeruginosa. We have investigated the optimal concentration of GQAs needed to eradicate preexisting biofilms and manage wound infections caused by P. aeruginosa, in vitro and in vivo. Results Our results revealed that GQAs exhibited 25–40 mm inhibition zone diameters, with 1–4 µg/mL MIC and 2–16 µg/mL MBC values. GQAs interfered with the planktonic mode of P. aeruginosa isolates, and significantly inhibited their growth in the pre-formed biofilm architecture, with MBIC80 and MBEC80 values of 64 µg/mL and 128 µg/mL, respectively. The anti-biofilm effect was confirmed by fluorescence staining and confocal microscopy which showed a dramatic reduction in the cell viability and the biofilm thickness (62.5%), after exposure to 128 µg/mL of GQAs in particular. The scanning electron micrographs showed that GQAs impaired biofilm and bacterial structures by interfering with the biomass and the exopolysaccharides forming the matrix. GQAs also interfered with virulence factors and bacterial motility, where 128 µg/mL of GQAs significantly (p < 0.05) reduced rhamnolipid, pyocyanin, and the swarming motility of the organism which play a vital role in the biofilm formation. GQAs downregulated 89% of the quorum-sensing genes (lasI and lasR, pqsA and pqsR) involved in the biofilm formation. Conclusion GQAs demonstrate significant promise as novel and potent antibiofilm and antivirulence agents against clinical isolates of MDR P. aeruginosa, with substantial potential to enhance wound healing in biofilm-associated infections. This promising antibacterial action positions GQAs as a superior alternative for the treatment of biofilm-associated wound infections, with substantial potential to improve wound healing and mitigate the impact of persistent bacterial infections. Clinical trial number not applicable.